Design and Implementation of C III Filter for Measuring Disruption in Aditya Tokamak. (October 2019) - Jegan Antony Marcilin, L.; Nandhitha, N.M.; Sam, Gayathri; Gladies Jaya Chitra, M.
Abstract: The main objective of this project is to filter carbon gas among many other gases emitted from the plasma in Aditya Tokamak. The aim is to measure the disruptions released by plasma due to some unpredictable conditions. C3 filter detects carbon gases from the various gases emitted from the plasma in Aditya Tokomak. The filter is to be designed with 5-6 layers of the material chosen. Then the signal segmentation for transmittance vs. wavelength is to be achieved using MATLAB software.